Effect of moisture contamination in gear oil lubricant on Yamaha outboard engine performance / Muhammad Haziq Hilmy Ismail - Ismail, Muhammad Haziq Hilmy (2022)
The moisture content in lubrication oil refers to the amount of water in the oil. Moisture content has a negative impact on lubricating oil and engine surface. The study was conducted to evaluate the methodologies used and the most effective approach for determining moisture content. The Fourier Transform Infrared (FTIR) analysis are the methods used. The techniques will be used to figure out the best way to measure moisture. The FTIR analysis result will be displayed on the machine we used. As a result of the findings, I believe I now know the best and easiest method for evaluating moisture content in lubricant oil. The methods used each have their own set of benefits and disadvantages.